Wild animals connect us with nature: about awe, eco-pedagogy, and nature-connectedness - Theresa S. S. Schilhab; Gertrud L. Esbensen (Frontiers in Psychology)
In recent years, studies have linked children’s experiences with nature to their understanding of sustainability. According to existing research, positive nature interactions and the experience of being part of nature motivate sustainable actions, a relationship described by the concept of “connectedness with nature.” Current research often refers to nature as a green (or blue) area—i.e., a place that, unlike urban areas, has characteristics that stimulate positive experiences of nature. Hence, the connection between experiences with local wild animals in nature (invertebrates such as snails and spiders, and vertebrates such as mammals and amphibians) and positive nature experiences remains unexplored. We do not yet know whether wild animals, as creatures with their own goals and worlds of experience, can stimulate children’s experience of being part of nature and ultimately lead to sustainable behaviour. However, animals are relatively easy to connect with and care for because their actions often resemble ours. This recognisability may intuitively pique children’s interest and thus initiate a budding emotional attachment to and understanding of nature. This article offers a theoretical framework for how children’s experiences of local wildlife may influence their opportunities to develop nature connectedness. The article demonstrates how observations of wild animals and their purposefulness in their natural environment potentially stimulate emotions and cognitions that are of significance to developing nature connectedness. We point to three effects, as follows: (1) the stimulation of curiosity through animals’ senses and actions, (2) insight into the diversity of nature through animals’ recognisable, yet different behaviour, and (3) the experience of how we depend on the concrete environment by proxy. We elaborate on the implications of these effects on children’s connection to nature. We also discuss the importance of adult involvement and support in the facilitation of certain feelings and cognitions in the development of children’s connectedness to nature.